Current Demographic Status of Cardiologists in the United States - Mehta, Laxmi S. (JAMA Cardiol, 2019)
IMPORTANCE: Increasing cardiology workforce diversity will expand the talent of the applicant pool and may reduce health care disparities. OBJECTIVE: To assess US cardiology physician workforce demographics by sex and race/ethnicity in the context of the US population and the available pipelines of trainees. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study used data from the Association of American Medical Colleges, the American Medical Association, and the American Board of Internal Medicine to stratify medical students, resident physicians, fellows, and cardiologists by sex and race/ethnicity. Additionally, proportional changes from 2006 through 2016 were assessed for adult and pediatric cardiology. Data analysis took place from August 2018 to January 2019. MAIN OUTCOMES AND MEASURES: Percentage of cardiologists and trainees by sex and race/ethnicity in 2016, as well as changes in proportions between 2006 and 2016. RESULTS: Despite a high percentage of female internal medicine resident physicians (10 765 of 25 252 [42.6%]), female physicians were underrepresented in adult general cardiology fellowships (584 of 2720 [21.5%]) and procedural subspecialty fellowships (interventional cardiology, 30 of 305 [9.8%]; electrophysiology, 24 of 175 [13.7%]). The percentage of female adult cardiologists slightly increased from 2006 through 2016 (from 8.9% to 12.6%; slope, 0.36; P < .001) but remained low. Female physicians made up a disproportionately higher number of pediatric residency positions (6439 of 8832 [72.9%]). Trends showed an increase in female pediatric cardiology fellows (from 40.4% to 50.5%; slope, 1.25; P < .001), which resulted in an increase in the percentage of female pediatric cardiologists (from 27.1% to 34.0%; slope, 0.64; P < .001). The percentages of members of underrepresented minority groups in adult and pediatric cardiology fellowships (from 11.1% to 12.4%; slope, 0.15; P = .01; and from 7.7% to 9.9%; slope, 0.29; P = .009; respectively) were low and increased only slightly over time. Additionally, members of underrepresented minorities made up less than 8% of practicing adult and pediatric cardiologists. Although Asian individuals are 5.2% of the US general population, they are not considered underrepresented because they are 22.1% of US medical school graduates (n = 4202 of 18 999), 38.1% of internal medicine resident physicians (n = 9618 of 25 252), 40.4% of adult cardiology fellows (n = 1098 of 2720), 19.9% of adult cardiologists (n = 5973 of 30 016), 22.6% of pediatric resident physicians (n = 1998 of 8832), 28.0% of pediatric cardiology fellows (n = 122 of 436), and 20.1% of pediatric cardiologists (n = 574 of 2860). CONCLUSIONS AND RELEVANCE: Female physicians remain underrepresented in adult cardiology, despite a robust pipeline of female medical students and internal medicine resident physicians. Women in pediatric cardiology are underrepresented but increasing in number. Members of several racial/ethnic minority groups remain underrepresented in adult and pediatric cardiology, and the percentages of trainees and medical students from these groups were also low. Different strategies are needed to address the continuing lack of diversity in cardiology for underrepresented minority individuals and women.